Toward a novel dosimetry system using acrylic disk radiation sensor for proton pencil beam scanning. Issue 11 (27th September 2018) - Cho, Shinhaeng; Lee, Nuri; Song, Sanghyeon; Son, Jaeman; Kim, Haksoo; Jeong, Jong Hwi; Lee, Se Byeong; Lim, Youngkyung; Moon, Sunyoung; Yoon, Myonggeun; Shin, Dongho
Abstract : Purpose: Fabricate an acrylic disk radiation sensor (ADRS) and characterize the photoluminescence signal generated from the optical device as basis for the development and evaluation of a new dosimetry system for pencil beam proton therapy. Methods: Based on the characteristics of the proposed optical dosimetry sensor, we established the relation between the photoluminescence output and the applied dose using an ionization chamber. Then, we obtained the relative integral depth dose profiles using the photoluminescence signal generated by pencil beam irradiation at energies of 99.9 and 162.1 MeV, and compared the results with the curve measured using a Bragg peak ionization chamber. Results: The relation between the photoluminescence output and applied dose was linear. In addition, the ADRS was dose independent for beam currents up to 6 Gy/min, and the calibration factor for energy was close to 1. Hence, the energy dependence on the optical device can be disregarded. The integral depth dose profiles obtained for the ADRS suitable agreed with the curve measured in the Bragg peak ionization chamber without requiring correction. Conclusions: These results suggest that the ADRS is suitable for dosimetry measurements in pencil beam scanning, and it will be employed as a low‐cost and versatile dosimetry sensor in upcoming developments.